Modelo de logística interna para mipymes del sector calzado en Bogotá, estudio de caso (2018)
In the development of the research project, it is proposed to work on a first step in a descriptive phase in which an identification of authors, models and success cases of internal logistics is made, and a triangulation study is carried out for success cases in the footwear sector based on national and international companies; with the purpose of identifying in each of these the main factors applied to authors, models and success stories. As a second phase of the research, an exploratory phase is carried out where the diagnosis and characterization of the footwear sector is carried out through the analysis of macroeconomic variables and the state of internal logistics from secondary sources such as articles, books, previous investigations, reports from financial entities such as the republic bank, state entities such as the DANE and industry associations such as ACICAM; this in order to analyze in detail the current situation of this and how has been its behavior in recent years. Additionally, it is proposed to carry out an analysis and prioritization of the causes of internal logistics failures in MSMEs through the implementation of dynamic hypotheses.